The highland tadpole of the harlequin frog Atelopus carrikeri (Anura: Bufonidae) with an analysis of its microhabitat preference (2015)
ABSTRACT: We describe the gastromyzophorous tadpole of Atelopus carrikeri, a harlequin frog endemic to the Sierra Nevada de Santa Marta, Colombia. In external morphology and colouration, this tadpole is similar to congeneric larvae with highland distributions yet distinct by its remarkable large size, having a well-developed suctorial ventral disc, and the upper lip usually having bilateral anterior projections that form a conspicuous M-shape. Tadpoles of this species inhabit fastflowing streams above 3,000 m in altitude where they attach themselves to submerged rocks, especially in areas with low algae cover.